แนวทางในการออกแบบโรงพยาบาลที่เอื้อต่อการเยียวยาสุขภาพแบบองค์รวม กรณีศึกษาโรงพยาบาลราชพฤกษ์ ขอนแก่น - อัศวบุญญาเดช อภิเชษฐ์ (สิ่งแวดล้อมสรรค์สร้างวินิจฉัย, 2015)
ความเจ็บป่วยเป็นปัญหาสำคัญที่ทุกคนไม่สามารถหลีกเลี่ยงได้ คนจำนวนไม่น้อยต้องรักษาตัวที่โรงพยาบาลเป็นประจำ และอีกหลายคนต้องใช้เวลาในช่วงสุดท้ายของชีวิตในโรงพยาบาล การออกแบบโรงพยาบาลจึงเป็นเรื่องที่สำคัญ สถาปนิกในฐานะที่มีหน้าที่ในการออกแบบ โรงพยาบาลจึงจำเป็นต้องคำนึงถึงการออกแบบให้ผู้ป่วยมีคุณภาพชีวิตที่ดี จึงได้นำแนวคิด เรื่องการเยียวยา “สุขภาพแบบองค์รวม” ซึ่งกล่าวถึงความเชื่อมโยงของมิติทางด้านกาย จิตใจ สังคม และสิ่งแวดล้อมที่เป็นอันหนึ่งอันเดียวกันในการรักษามาใช้เป็นโจทย์ในการศึกษาวิจัย โดยใช้ระเบียบวิจัยเชิงปฏิบัติการ (Action Research) ในการสร้างกระบวนการมีส่วนร่วมกับเจ้าของโครงการและผู้ใช้โครงการในการศึกษาแนวทางการออกแบบโรงพยาบาลที่เอื้อต่อการเยียวยาสุขภาพแบบองค์รวม และนำแนวทางการออกแบบมาประยุกต์ใช้ในการออกแบบโรงพยาบาลราชพฤกษ์ จังหวัดขอนแก่น รวมทั้งมีการประเมินผลการออกแบบโรงพยาบาลร่วมกับเจ้าของโครงการและผู้ใช้โครงการ Designing of the Holistic Health Healing Hospital : A Case Study of Rachapreuk Hospital, Khon Kaen Apichet Assawabunyadej The illness is the significant trouble that nobody can avoid. A considerable number of people receive treatment at the hospital regularly while many spend their last moment of life in the there. Therefore, the hospital design is essential. As the architect who is responsible for the hospital design, the design that will promote the patients to have good quality of life must be considered. The researcher has adopted the concept of healing “Holistic Health” which mentions about the correlation of the dimensions of body, mind, society, and environment which is unified in the treatment as the subject of the research. Implement the Action Research model by creating the participation procedures between the project owner and the project users as the study for the designing of the Holistic Health Healing hospital; the design guideline are adapted in the design of Rachapreuk Hospital, Khon Kaen, including co-evaluate the hospital design together with the owner and users.